Multi-target approach of Egyptian leek extract in ameliorating depressive-like behavior in rats exposed to chronic unpredictable mild stress - Mahmoud, Mai M. S.; Essawy, Amina E.; Soffar, Ahmed A.; Faraag, Ahmed H. I.; Dkhil, Mohamed A.; Ahmed-Farid, Omar A.; El-Khadragy, Manal F.; Abdel Moniem, Ahmed E. (Frontiers in Pharmacology, 2025)
IntroductionDepression is a widespread and debilitating disorder with a complex etiology involving oxidative stress, neuroinflammation, and apoptosis. Given the limitations of current treatments, there is an urgent need for alternative therapeutic approaches. This study evaluated the antidepressant effects of Egyptian leek (Allium ampeloprasum var. kurrat) in rats exposed to chronic unpredictable mild stress (CUMS), a well-established model for studying depression, while exploring the underlying molecular mechanisms. Egyptian leek extract is rich in bioactive compounds, including flavonoids, alkaloids, terpenoids, steroids, and saponins, which are known for their neuroprotective and mood-regulating properties.MethodsUsing liquid chromatography-mass spectrometry (LC-MS) and Fourier-transform infrared spectroscopy (FT-IR), the leek extract was analyzed to identify bioactive compounds. In this study, CUMS-exposed rats were treated with the extract, and their behavior was assessed using the sucrose preference test (SPT), open field test (OFT), and social interaction test (SIT). Concurrently, oxidative stress and antioxidant factors, pro-inflammatory cytokines, and apoptotic proteins in the cerebral cortex were evaluated, and molecular docking analyses were conducted to investigate the extract’s mechanisms of action.ResultsThe results demonstrated that treatment with Egyptian leek extract significantly alleviated depression-like behaviors, as evidenced by improved performance in the SPT, OFT, and SIT. Moreover, the leek extract improved oxidative stress parameters, reduced levels of pro-inflammatory cytokines, suppressed NF-κB activation, and promoted neuronal survival by modulating apoptosis-related proteins.DiscussionThese results suggest that the leek extract effectively mitigates oxidative stress, inflammation, and apoptosis, thereby contributing to its overall antidepressant effects.